Extraction of Polycyclic Aromatic Hydrocarbons from Water Samples into a Rotating-Disk Microextractor and the Subsequent Determination by Gas Chromatography-Mass Spectrometry - Rubio-Campos, M (Sociedad Chilena de Quimica, 2014)
The rotating disk sorptive extraction (RDSE) technique was applied in this study to the extraction of 16 polycyclic aromatic hydrocarbons (PAHs) in real water samples. The sorptive and desorptive behavior of the analytes were studied by using a rotating disk coated with polydimethylsiloxane (PDMS) on one of its surfaces. The optimal conditions for extractions of all analytes were: rotational velocity of the disk: 1250 rpm; sample volume: 20 mL; matrix modifier: 20% MeOH and extraction time: 30 min. A desorption time of 10 min at 1250 rpm was used for the analytes using 5 mL of methanol. PAHs were measured in the extract by gas chromatography coupled to mass spectrometry (GC-MS). Under these conditions, recoveries ranging from 84 to 100% were obtained in drinking water enriched with the analytes, and the precision, expressed as relative standard deviation, was between 2 and 20%. The detection limit of the method was between 8 and 115 ng L-1depending on the analyte. The method was applied to the analysis of water samples obtained from a lagoon in Curauma, Chile, obtaining quantitative recoveries. © 2014, Sociedad Chilena de Quimica. All rights reserved.